Synergism of the receptor tyrosine kinase Axl with ErbB receptors mediates resistance to regorafenib in hepatocellular carcinoma - Breitenecker, Kristina; Hedrich, Viola; Pupp, Franziska; Chen, Doris; Řezníčková, Eva; Ortmayr, Gregor; Huber, Heidemarie; Weber, Gerhard; Balcar, Lorenz; Pinter, Matthias; Mikulits, Wolfgang (Frontiers in Oncology, 2023)
Introduction: Hepatocellular carcinoma (HCC) patients at advanced stages receive immunotherapy or treatment with tyrosine kinase inhibitors (TKIs) such as Sorafenib (Sora) or Lenvatinib in frontline as well as Regorafenib (Rego) or Cabozantinib in second-line. A major hindrance of TKI therapies is the development of resistance, which renders drug treatment futile and results in HCC progression.In this study, we addressed the impact of the receptor tyrosine kinase Axl binding to its ligand Gas6 in acquiring refractoriness to TKIs. The initial responses of Axl-positive and Axl-negative cell lines to different TKIs were assessed. Upon inducing resistance, RNA-Seq, gain-and loss-offunction studies were applied to understand and intervene with the molecular basis of refractoriness. Secretome analysis was performed to identify potential biomarkers of resistance.We show that HCC cells exhibiting a mesenchymal-like phenotype were less sensitive to drug treatment, linking TKI resistance to changes in epithelial plasticity. Gas6/Axl expression and activation were upregulated in Rego-resistant HCC cells together with the induction of ErbB receptors, whereas HCC cells lacking Axl failed to stimulate ErbBs. Treatment of Rego-insensitive HCC cells with the pan-ErbB family inhibitor Afatinib rather than with Erlotinib blocking ErbB1 reduced cell viability and clonogenicity. Genetic intervention with ErbB2-4 but not ErbB1 confirmed their crucial involvement in refractoriness to Rego. Furthermore, Rego-resistant HCC cells secreted basic fibroblast growth factor (bFGF) depending on Axl expression. HCC patients treated with Sora in first-line and with Rego in second-line displayed elevated serum levels of bFGF, emphasizing bFGF as a predictive biomarker of TKI treatment.Discussion: Together, these data suggest that the inhibition of ErbBs is synthetic lethal with Rego in Axl-expressing HCC cells, showing a novel vulnerability of HCC.